Tinjauan Yuridis Penerapan Tindakan Keberi Kimia Terhadap Pelaku Persetubuhan Pada Anak Di Kejaksaan Negeri Kabupaten Bogor - Fahmi Azis; Febby Irwani; Bayu Eka Putra; Vikram Surya Husada (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
Indonesia has ratified the Convention on the Rights of the Child which means that Indonesia is bound by international law to implement provisions in the CRC to adopt legislative, administrative and programmatic measures to ensure children's rights are realized with the issuance of Government Regulation in Lieu of Law Number 1 Year 2016 which was passed into law as the second revision to Child Protection Law Number 23 of 2002 on Child Protection. The ratification of Government Regulation in Lieu of Law Number 1 Year 2016 is a form of crunch against the high cases of child sex abuse because the criminal sanctions imposed on perpetrators of child sexual abuse have not had a deterrent effect and have not been able to comprehensively prevent the occurrence of sexual violence against children, so it is necessary to immediately amend Law Number 23 of 2002 on Child Protection. Government Regulation in Lieu of Law Number 1 Year 2016 imposes sanctions for perpetrators of sexual crimes that add to the basic penalty of death and life imprisonment and additional criminal acts of chemical castration, the addition of provisions on the act of chemical castration is a form of legal reform because punishing violators with the death penalty is no longer constitutional and those who are released often return and end up in prison, therefore it is necessary to find other rule of law and humane methods to treat these offenders.